2009
DOI: 10.1007/s11695-009-9874-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Radiological Gastric Capacity and Evolution of the BMI 2–3 Years After Sleeve Gastrectomy

Abstract: Gastric capacity can increase late after sleeve gastrectomy even after performing a narrow gastric tubulization. It is very important to measure objectively residual gastric volume after sleeve gastrectomy and its eventual increase in order to determine the late clinical results and to indicate eventual strategy for retreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 17 publications
7
46
1
4
Order By: Relevance
“…This initial volume is in accordance with a volume of 116 ml after LSG that has been reported by also using a 32-Fr calibration tube [7]. In another study, a slightly higher volume of 135 ml was found by means of saline instillation and manometric measurements after LSG with a calibration size of 50 Fr [12].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This initial volume is in accordance with a volume of 116 ml after LSG that has been reported by also using a 32-Fr calibration tube [7]. In another study, a slightly higher volume of 135 ml was found by means of saline instillation and manometric measurements after LSG with a calibration size of 50 Fr [12].…”
Section: Discussionsupporting
confidence: 87%
“…The estimation of the sleeve stomach volume from upper gastrointestinal series was attempted but abandoned in one study due to the technical challenges and lack of correlation with direct intraoperative measurements [12]. Successful volumetric assessment after LSG by MSCT has been reported by two studies, with a marked dilation of the sleeve being found in an intraindividual comparison of 15 patients during follow-up [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En el seguimiento de pacientes con manga gástri-ca, Braghetto y cols, ha descrito que con el paso del tiempo existe importante aumento de la capacidad de la manga, evaluando con técnicas radiológicas e isotópicas. Al comparar imágenes postoperatorias precoces de la capacidad de la manga calibrada con bujías 32, con imágenes del mismo paciente tomadas años después, se ha encontrado una capacidad del tubo gástrico significativamente mayor 13 . Los aspectos hormonales también han sido considerados.…”
Section: Reganancia De Pesounclassified